Ethical considerations when caring for the older adults: a review of the international research - Nguyễn, Tuấn Vinh (Đại học Quốc gia Hà Nội, 2020)
This study explores the ethical guidelines in working with older adults. In order to generate a sophisticated understanding of this phenomenon, a literature review is adopted as the primary research design for the study. The results conclude that older adult population is increasing in many countries including Vietnam, which indeed is one of ten countries with the world's fastest rate of ageing. Moreover, the increased number of older adults is correlated with increased health problems and complex ethical issues.